Implementasi Program Pembiasaan Literasi Agama dalam Mencegah Perilaku Judi Online Pada Mahasiswa UNMUH Bangka Belitung - Tohir, Muhamad; Hevitria, Hevitria (UIR Press, 2025)
Online gambling is now widespread, even among college students. Online slot games fall into the category of gambling that uses money as stakes. In this type of game, players purchase chips to use in betting. Religious literacy serves as a practice that helps individuals understand religious teachings across different cultural settings. Religious literacy encompasses more than just knowledge or skills about the teachings and practices of a particular religion. Technology has become a crucial element in society in this digital age. This study aims to introduce students to religious literacy programs, so that by introducing religious literacy, online gambling can be reduced. Implementing religious literacy among students on campus aims to address negative behavior related to gambling. Religious literacy needs to be taught to students so they can live in today's modern society. The religious literacy movement is an activity that focuses on sources of information related to religion. Religious literacy is closely related to students' religious character. This research is quantitative, providing a religious literacy habituation program for students. Participants in this study consisted of several students from the State Islamic University of Babel (UNMUH Babel). Data collection instruments included observation sheets, interviews, and questionnaires. The research findings indicate an increase in students' understanding of judol (Islamic gambling). This improvement is expected to reduce the likelihood of becoming entangled in online gambling practices in the future.